Gut microbiota: A protective mechanism against tuberculosis in children with household contacts in a TB-endemic environment - Hapsari, Rika; Endaryanto, Anang; Mertaniasih, Ni Made; Setyoningrum, Retno Asih; Chafid, Arda Pratama Putra; Hamida, Azizah (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The gut-lung axis has contributed to the impairment of pulmonary infectious diseases. Gut microbiota appears to play a crucial role in modulating host immunity against tuberculosis (TB) infection in children. We examined the gut microbiota in children with tuberculosis and those who were in close contact and residing in the same household.Methods: A cross-sectional study was conducted involving patients aged from 1 month to 18 years who were diagnosed with bacterial confirmation of tuberculosis. Contact investigations were conducted for all patients. The sibling residing in the same household underwent screening for tuberculosis using a tuberculin test. Fecal samples were obtained from two groups upon admission. Next-generation sequencing was utilized to analyze the 16sRNA of the samples.Results: This study showed a notable decrease in the relative abundance of the phylum Bacillota was observed in children with TB disease compared to those exposed to TB. The diversity of microbiota is altered, as indicated by a decrease in both the Shannon index and the Simpson's index in children with TB disease.Conclusions: The gut microbiota in children with TB disease exhibited distinct differences compared to those exposed to TB, particularly in terms of the relative abundance of bacteria. This work will provide an understanding of gut microbiota influence on control mechanisms of TB infection in children.